2015
DOI: 10.1074/jbc.m114.628131
|View full text |Cite
|
Sign up to set email alerts
|

Upstream Binding of Idling RNA Polymerase Modulates Transcription Initiation from a Nearby Promoter

Abstract: Background:The fis promoter upstream region harbors RNA polymerase binding sites of unknown function. Results: Modifications of the upstream polymerase binding affect fis gene expression in a supercoiling-dependent manner. Conclusion: Concomitant binding of RNA polymerase at the fis promoter and upstream region acts as a topological device regulating transcription. Significance: RNA polymerase can act as an architectural factor modulating the activity of transcription initiation complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 82 publications
1
17
0
Order By: Relevance
“…Unlike the inducible lac promoter, fis promoter activity is exquisitely sensitive to changes of DNA supercoiling, due in part to the GC-rich discriminator sequence between the −10 hexamer and the transcription start site ( 45 ), which mediates the growth phase- and growth rate-dependent control ( 26 , 28 ). This sensitivity to supercoiling might also be related to the observations that the fis promoter region, highly conserved in all pathogenic E. coli and Shigella strains, is characterized by strong intrinsic curvature ( 46 ), is regulated by a higher-order RNA polymerase complex involved in sensing the topological state of DNA ( 41 , 44 ) and appears evolutionarily streamlined to act as a topological switch ( 47 , 48 ). Some or all of these differences could contribute to disparate effects exerted by the insertions of lac and fis promoter constructs on their immediate surroundings.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Unlike the inducible lac promoter, fis promoter activity is exquisitely sensitive to changes of DNA supercoiling, due in part to the GC-rich discriminator sequence between the −10 hexamer and the transcription start site ( 45 ), which mediates the growth phase- and growth rate-dependent control ( 26 , 28 ). This sensitivity to supercoiling might also be related to the observations that the fis promoter region, highly conserved in all pathogenic E. coli and Shigella strains, is characterized by strong intrinsic curvature ( 46 ), is regulated by a higher-order RNA polymerase complex involved in sensing the topological state of DNA ( 41 , 44 ) and appears evolutionarily streamlined to act as a topological switch ( 47 , 48 ). Some or all of these differences could contribute to disparate effects exerted by the insertions of lac and fis promoter constructs on their immediate surroundings.…”
Section: Discussionmentioning
confidence: 92%
“…The repositioned operon contained the promoter upstream sequences comprising all the known binding sites for regulatory proteins involved in fis transcriptional control ( 39 41 ). We used the entire operon instead of the fis gene, because the upstream dusB ORF is absolutely required for efficient translation of the fis mRNA, as well as substituted reporter gene message ( 42 44 ). We observed that although the displaced operons quantitatively maintained the growth phase-dependent expression pattern and produced the same amount of FIS protein in the cell, the repositioning of the dusB-fis operon exerted pleiotropic effects on the expression of genes distant from the insertion site.…”
Section: Discussionmentioning
confidence: 99%
“…Topology-dependent binding enables DNA-binding proteins to discriminate between different sites in DNA 50 . For instance, HMG–containing and TATA binding proteins bind to untwisted DNA, and bacterial architectural proteins, such as HU and H-NS, as well as eukaryotic histones, bind and stabilize -SC DNA 51 , 52 . Yet others, for example the bacterial FIS protein preferentially binds intermediate supercoiled DNA as compared with the extremes of the topological spectrum 53 ; the reverse is true for the tumor suppressor p53, which binds preferentially both −SC and +SC DNA, whereas it shows lower affinity for relaxed DNA 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that promoter-promoter interaction via TCDS is normally short-range 37 , the separation between PR1-1 and PR1-2 is around 132 bp, so the notion that transcription from PR1-1 can influence the activity of adjacent promoter PR1-2 on the same DNA chain though local supercoiling is therefore reasonable. In the fis promoter there are three tandem RNAP binding sites and it has been proposed that idling of RNAP at an upstream promoter acts as an accessory factor to stimulate transcription from the downstream promoter 38 . The observation that the mutation at position 2 of the -10 of PR1-1, prevented transcription from PR1-2, would argue against RNAP idling at PR1-1 being the mechanism by which PR1-2 is activated, since mutations at this site in the -10 region will not prevent RNAP binding and idling at the PR1-1 promoter 39 .…”
Section: Discussionmentioning
confidence: 99%